Morphological and molecular review of the Gekko diversity of Laos with descriptions of three new species - Luu, Vinh Quang; Calame, Thomas; Nguyen, Truong Quang; Le, Minh Duc; Ziegler, Thomas (Zootaxa, 2015)
A review of the taxonomy, phylogeny, zoogeography, and ecology of the genus Gekko in Laos is provided based on morphological and molecular datasets. Three new species, which are both morphologically distinctive and molecularly divergent from described congeners, are described from Khammouane Province, central Laos: two members of the G. japonicus group, Gekko bonkowskii sp. nov. and Gekko sengchanthavongi sp. nov., and another member of the G. petricolus group, Gekko boehmei sp. nov. Gekko bonkowskii sp. nov. is closely related to the recently described G. thakekensis, which also occurs in Khammouane Province. Gekko sengchanthavongi sp. nov. is supported as a sister taxon to G. scientiadventura and Gekko boehmei sp. nov. is recovered as a sister species to G. petricolus. In addition, a key to the currently recognized members of the genus Gekko from Laos is provided.